It takes two to tango: how large the effects of job factors on wife’s work-family conflict? - Afifah Idris,; Rosnah Ismail, (Jabatan Kesihatan Masyarakat, Pusat Perubatan Universiti Kebangsaan Malaysia, 2018)
Introduction Married couples often do influence each other’s emotions and behaviors. The effect of this interpersonal marriage relationship on emotional job demands and job performance toward work-family conflict (WFC) is still under research. This article aims to determine the effects of married couple’s job factors (emotional job demands and job performance) on wife’s WFC. Methods A total of 120 dyads in private sectors were recruited via private invitations to social gatherings. Packets of self-administered questionnaires were given included emotional domain of Demand-Induced Strain Compensation, Spielberger Trait Anger Scale, work-family conflict and job performance measures. Dyadic analysis using Actor-Partner Interdependence Model was used. Results The emotional demand of wife significantly contribute higher effect (ES= 0.34 (95%CI: 0.23, 0.45); p<0.001) compared to emotional job demand of husband on wife’s WFC (ES= 0.14 (95%CI: 0.03, 0.25); p=0.011). The job performance of wife significantly contribute higher effect (ES= 0.29 (95%CI: 0.17, 0.40); p<0.001) compared to job performance of husband on the wife’s WFC (ES= 0.17 (95%CI: 0.06, 0.29); p=0.003). Both wife and husband influenced each other pertaining to emotional job demands (r=0.35, 95%CI: 0.22, 0.48) and job performance (r=0.51, 95%CI: 0.38, 0.64) on the wife’s WFC. Overall, the APIM model explains of 22.9% and 25.1% of the total of non-independence of emotional job demands and job performance toward WFC, respectively. Conclusions Wife’s WFC was influenced by both herself and her partner’s emotional job demands and performance. All resources should be channeled to working wives to prevent any health and job outcomes resulted from the work-family conflict.